2012
DOI: 10.1177/1461444811431864
|View full text |Cite
|
Sign up to set email alerts
|

Transcoding the news: An investigation into multimedia journalism published on nytimes.com 2000–2008

Abstract: Manovich (2001) describes the changes that result from translating an established cultural product into a new technology as ‘transcoding’. This study investigates the form that the journalism of The New York Times takes when transcoded to the Web by evaluating multimedia news packages published on nytimes.com from 2000–2008. The number and sophistication of the multimedia packages grew over time to include new interfaces that incorporated elements native to digital environments such as hypertextual links, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 16 publications
1
25
0
9
Order By: Relevance
“…After identifying the packages to be used for analysis, we turned to previous research that identifies common characteristics in journalism and used these characteristics of storytelling to construct a codebook (Darnton, 1975;Gutsche and Salkin, 2013;Jacobson, 2012;Manoff, 1986;Pfau et al, 2004;Schudson, 2005;Sims, 2007).…”
Section: Methodsologymentioning
confidence: 99%
“…After identifying the packages to be used for analysis, we turned to previous research that identifies common characteristics in journalism and used these characteristics of storytelling to construct a codebook (Darnton, 1975;Gutsche and Salkin, 2013;Jacobson, 2012;Manoff, 1986;Pfau et al, 2004;Schudson, 2005;Sims, 2007).…”
Section: Methodsologymentioning
confidence: 99%
“…As news has evolved, journalists have experimented with new formats to enhance and transform the news consumption experience (Barnhurst, 2010;Pauly, 2014). Multimedia journalism refers to stories in which more than two media models are utilized, such as text, images, and video (Pincus et al, 2016;Harper, 2005;Jacobson, 2012;Deuze, 2004). Multimedia journalism is an important shift in thinking about a different, more visual and participative way of news reporting.…”
Section: Journalism Meets Technologymentioning
confidence: 99%
“…The studies (Jacobson, 2012) also suggested that online journalism has the potential to incorporate new forms of expression but news organizations have yet to fully embrace these features.…”
Section: Professional Journalistic Conceptmentioning
confidence: 99%